2017
DOI: 10.1002/lary.26683
|View full text |Cite
|
Sign up to set email alerts
|

Treatment disparities in the management of epistaxis in United States emergency departments

Abstract: 2C. Laryngoscope, 128:356-362, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 23 publications
0
43
0
1
Order By: Relevance
“…The authors postulated that increased packing rates could indicate reduced availability of otolaryngologic services. 16 Patients admitted on a weekday were more likely to receive early intervention for nosebleed than those admitted on a weekend (OR, 1.86; 95% CI, 1.34-2.58). 36 In addition, admission to an urban hospital more often resulted in embolization or surgical ligation, likely due to increased availability of specialty services, but an increase in the likelihood of embolization specifically was not seen.…”
Section: Cost and Variations In Carementioning
confidence: 98%
See 1 more Smart Citation
“…The authors postulated that increased packing rates could indicate reduced availability of otolaryngologic services. 16 Patients admitted on a weekday were more likely to receive early intervention for nosebleed than those admitted on a weekend (OR, 1.86; 95% CI, 1.34-2.58). 36 In addition, admission to an urban hospital more often resulted in embolization or surgical ligation, likely due to increased availability of specialty services, but an increase in the likelihood of embolization specifically was not seen.…”
Section: Cost and Variations In Carementioning
confidence: 98%
“…24 In the study of epistaxis patients using NEDS, 15% of patients were on long-term anticoagulation, 33% had a history of hypertension, and 0.9% had an underlying coagulation disorder. 16 The often-assumed causal relationship between epistaxis and hypertension is not well established. 18 A recent systematic review of the association of hypertension with epistaxis showed an association of hypertension with epistaxis (odds ratio [OR], 1.532; 95% confidence interval [CI], 1.181-1.986), but no study supported any causal relationship.…”
Section: Health Care Burdenmentioning
confidence: 99%
“…and that 52.7% of them were male (13). In a study conducted by Kucik et al, it was stated that the incidence of epistaxis is higher in the male population (14).…”
Section: Discussionmentioning
confidence: 99%
“…The authors postulated that increased packing rates could indicate reduced availability of otolaryngologic services. 16 Patients admitted on a weekday were more likely to receive early intervention for nosebleed than those admitted on a weekend (OR, 1.86; 95% CI, 1.34-2.58). 36 Additionally, admission to an urban hospital more often resulted in embolization or surgical ligation, likely due to increased availability of specialty services, but an increase in the likelihood of embolization specifically was not seen.…”
Section: Cost and Variations In Carementioning
confidence: 98%